2014
DOI: 10.1155/2014/713170
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Acaricidal Activity ofAtropa belladonnaand Its Components, Scopolamine and Atropine, againstRhipicephalus(Boophilus)microplus

Abstract: In vitro efficacy of methanolic extract of Atropa belladonna and its components scopolamine and atropine was assessed against Rhipicephalus (Boophilus) microplus. Five concentrations of the extract (1.25%, 2.5%, 5%, 10%, and 20%) were used whereas scopolamine and atropine were each tested at 0.1%. In adult immersion test, the extract was lethal to ticks at 20% concentration. The LC50 and LC95 values were determined as 6.875% and 17.306%, respectively. The extract caused a significant reduction (P < 0.05) in eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…It shows that the quantities of eggs laid in the ticks treated decreased significantly (P <0.05) compared to the controls. These results corroborate with those of Godara et al (2014) who also found a 44.2% reduction in egg-laying with the methanolic extract of Atropa belladonna at 200 mg/mL. Similarly, another study showed more significant inhibitions of egg-laying of 96.9% and 89.3% at 200 mg/mL, respectively, with the ethanolic extract of Piper nigrum and Piper longum (Godara et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…It shows that the quantities of eggs laid in the ticks treated decreased significantly (P <0.05) compared to the controls. These results corroborate with those of Godara et al (2014) who also found a 44.2% reduction in egg-laying with the methanolic extract of Atropa belladonna at 200 mg/mL. Similarly, another study showed more significant inhibitions of egg-laying of 96.9% and 89.3% at 200 mg/mL, respectively, with the ethanolic extract of Piper nigrum and Piper longum (Godara et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Relative to hatching rates for laid eggs, O. gratissimum had a maximum value of 24% and L. oloptera, 91.3% at the concentration of 200 mg/mL. These results are in agreement with those of Godara et al (2014), who achieved 100% inhibition of egg hatching with the methanolic extract of Atropa belladonna at 100 mg/mL. Likewise, Parveen et al (2014) showed 100% inhibition with the ethanolic extract of Artemisia absinthium at only 50 mg/mL.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Along with use of hosts with natural resistance to ticks, use of biological control agents and tick vaccines, exploration of the possibilities of using botanical acaricides has been identified as the future options. Recently, work on development of herbal acaricides has been initiated in our laboratory and promising results were achieved against ticks infesting domestic animals (Godara et al 2014a(Godara et al , b, 2015.…”
Section: Discussionmentioning
confidence: 99%